SPEECHLESS Speaks Loudly in Stomatal Development - Chen, Liang; Wu, Zhongliang; Hou, Suiwen (Frontiers in Plant Science, 2020)
Stomata, the small pores on the epidermis of plant shoot, control gas exchange between the plant and environment and play key roles in plant physiology, evolution and global ecology. Stomatal development is initiated by the basic helix-loop-helix (bHLH) transcription factor SPEECHLESS (SPCH), whose central importance in stomatal development has recently come to light. SPCH integrates intralineage signals and serves as an acceptor of hormonal and environmental signals to regulate stomatal density and patterning during the development. SPCH also plays a direct role in regulating asymmetric cell division in the stomatal lineage. Owing to its importance in stomatal development, SPCH expression is tightly and spatiotemporally regulated. The purpose of this review is to provide an overview of the SPCH-mediated regulation of stomatal development, reinforcing the idea that SPCH is the central molecular hub for stomatal development.